Phase-resolved TeV gamma-ray characteristics of the Crab and Geminga pulsars - Aharonian, Felix A.; Akhperjanian, A. G.; Barrio, J. A.; Bernlöhr, Konrad; Bojahr, H.; Contreras, J. L.; Cortina, J.; Daum, A.; Deckers, T.; Denninghoff, S.; Fonseca, V; Gonzalez, J. C.; et al. (Astronomy and astrophysics, 1999)
The Crab and Geminga pulsars were observed with the HEGRA stereoscopic IACT-System. A search for phaseresolved time structure of TeV gamma emission was carried out for both pulsars. No evidence for pulsed emission was observed. Geminga shows up as a TeV quiet object in our data. Upper limits were derived in units of the observed DC TeV Crab ﬂux. The 3σ upper limit on DC TeV emission of Geminga is 13.0% of the Crab ﬂux. Upper limits on pulsed emission were derived for the phase intervals which revealed pulsed emission in the EGRET 30 MeV - 10 GeV data. The 3σ upper limits on pulsed emission in these phase intervals are <2.3% and <7.2% of the Crab DC ﬂux for the Crab and Geminga pulsars, respectively.
Gesehen am 24.11.2020